PEMBERDAYAAN MASYARAKAT DALAM PENGELOLAAN DAS MIKRO: KONSEP DAN IMPLEMENTASI - Dewi R Indrawati; San Afri Awang,; Lies Rahayu W Faida,; Ahmad Maryudi Maryudi (Jurnal Kawistara, 2016)
Community empowerment should more emphasis on community self-reliance. In practice, manycommunity development activities were not in accordance with the concept of community empowerment.This study aims to examine the implementation of community empowerment in watershed managementin Sub-watershed of Keduang. This research was conducted in three micro watersheds in Sub-watershedof Keduang, namely micro watershed of Naruan, Pohbener, and Jlegong. Data collection was donethrough Focus Group Discussion (FGD) and in-depth interviews. Analyses were conducted with aqualitative descriptive approach. The results shows that the community empowerment in watershedmanagement has not yet meet the concept of community empowerment and has not be able to be saidsuccessful, because the community does not have power or authority to take decisions autonomously.In addition, community participation is still the participation of consultation and the participationmobilized by incentives or assistance